Вплив пандемії COVID-19 на туристичну галузь: виклики та перспективи розвитку - Тараненко, Галина Григорівна; Михайлов, Володимир Вікторович; Taranenko, Halyna; Mikhailov, Volodymyr (Мелітополь : 2021, 2021)
UA: Проаналізовано сучасний стан розвитку індустрії туризму, що демонструвала стійкий розвиток останні десятиріччя, в умовах пандемії COVID-19. Обґрунтовано необхідність надання невідкладної підтримки суб’єктам галузі та створення умов для успішного відновлення їх діяльності в довгостроковій перспективі. Актуалізовано, що індустрія туризму стала гарним прикладом для аналізу та розуміння умов старту для відновлення у ситуації катастрофи. Акцентовано увагу на тому, що у ситуації, що склалася, особливо важливою стає поведінка учасників ринку та прийняті рішення на рівні держави. Доведено, що для учасників ринку важливим постає розуміння перспектив успішного розвитку екосистем бізнесу в умовах як конкуренції, так і взаємодопомоги, що є надзвичайно важливим для прогресивного розвитку будь-якої галузі, особливо в період кризи. Нарівні влади актуалізується питання усвідомлення того факту, що туризм є одним з двигунів відновлення економіки, зокрема за умови внесення змін до системи оподаткування та акценту на підтримці внутрішнього та в’їзного туризму. EN: The article analyzes the current state of the tourism industry development, which has demonstrated sustainable development in recent decades, in the context of the COVID-19 pandemic. The necessity of providing urgent support to the subjects of the branch and creation of the conditions necessary for the successful restoration of their activities in the long run is substantiated. It is stressed that the tourism industry has become a good example for analyzing and understanding the conditions essential for starting the restoration from a disaster. Emphasis is placed on the fact that in the current situation, the behavior of market participants and decisions made at the state level become especially important. It is proved that for market participants it is important to understand the prospects for successful development of business ecosystems in conditions of both competition and mutual assistance, which is extremely important for the progressive development of any industry, especially during the crisis period. At the same time, the authorities are raising awareness of the fact that tourism is one of the engines of the economic recovery, in particular, provided that changes should be made to the tax system and the emphasis must be placed on supporting domestic and inbound tourism. The article investigates the theoretical and practical principles of the tourism industry development problems in the conditions of the COVID-19 pandemic. The importance of the immediate support of the subjects of the branch and creation of the conditions necessary for the successful restoration of tourist activity in the long run is substantiated. The role of appropriate actions from both the market participants and the state has been proved. The article analyzes the key ways out of the crisis and highlights the priority ones. The purpose, tasks and main measures for the practical implementation of this strategy are defined. The necessity of conceptual revision of the content and philosophy of the tourism industry is substantiated.
The impact of the COVID-19 pandemic on the tourist industry: challenges and development prospects
Keywords: туризм; COVID-19; пандемія; криза; державна політика; філософія туристичної галузі; tourism; pandemic; crisis; public policy; philosophy of tourism industry